Online programming system for a robot / Halim Sammuri - Sammuri, Halim (2005)
This paper concern with the design of online programming system that program a robot before it can be used to do a desired job. The programming system was developed using visual basic software. After this task a program and robot can be uses at actual job or environment by loading a programming from database. Same with this project, it will program robots by human manually and then the desired program will be download to robot, lastly robots can run automatically. In this project ROB3 from EUROBTEC robot was used to interface a program. This thesis is all about the "Online Programming System for a Robot" using the Visual Basic 6.0